Analysis of the Use of Social Networks by Cultural Institutions During the Pandemic: Cases Museo de Arte de Lima and Gran Teatro Nacional - Navarro Hospinal, Susana (2021)
Digital tools are not new, but the pandemic has made visible the need for cultural institutions to establish new alternatives and digital has not only become a tool, but has become vital for the empowerment of museums and culture in general. According to Conseil International des Musées (ICOM), communication is often not a priority for cultural organi-zations, and even less so when it comes to digital, specifically social networks (2019, p. 5). An analysis was made of the digital responses of two Peruvian institutions, the Museo de Arte de Lima (MALI) and the Gran Teatro Nacional (GTN), to determine how their presence in social networks and on the web evolved. For this purpose, we also talked to the people in charge of the communication areas of these institutions.